Retirement and changes in housework: A panel study of dual earner couples - Thomas Leopold; Jan Skopek (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
To examine how transitions to retirement influenced the division of household labor in dual earner couples. We tested hypotheses about changes (a) between a couple's pre-retirement and post-retirement stage, and (b) across the transitionalphase during which both spouses retired from the workforce. We estimated fixed-effects models for the effects of the husband's and the wife's retirement on changes in their hours and share of routine housework. The data came from 29 waves of the German Socio-economic Panel Study, comprising N = 27,784 annual observations of N = 3,071 dual earner couples ages 45 to 75. Spouses who retired first performed more housework, whereas their partners who continued working performed less. This occurred irrespective of the retirement sequence. Husbands who retired first doubled up on their share of housework, but never performed more than 40 percent of a couple's total hours. None of the observed shifts was permanent. After both spouses had retired, couples reverted to their pre-retirement division of housework. Although the findings on changes after retirement support theories of relative resources, gender construction theories still take precedence in explaining the division of household labor over the life course.
Keywords: 330